2007
DOI: 10.4067/s0718-16202007000200004
|View full text |Cite
|
Sign up to set email alerts
|

Stability of anthocyanin in spinach vine (Basella rubra) fruits

Abstract: E. Ferreira Ozela, P. César Stringheta, and M. Cano Chauca. 2007. Stability of anthocyanin in spinach vine (Basella rubra) fruits. Cien. Inv. Agr 34(2):115-120. The stability of anthocyanin in the extract of spinach vine fruit (Basella rubra L.) was studied in relation to degradative factors such as light, temperature and pH acting alone or in combination. In this work, the possible use of spinach vine fruit as a source of natural pigments for use in food coloring was evaluated. Extraction of the pigment was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…Brazilian Journal of Development, Curitiba, v.9, n.3, p. 10783-10798, mar., 2023 It was observed that the reddish hue (a*) increased during storage, showing a significant difference on all evaluated days. This fact is desirable since anthocyanins present the possibility of replacing the artificial dyes Red 40, Ponceau 4R, Erythrosine and Bordeaux S (Ozela et al, 2007).…”
Section: Stability Of the Powder Dye During Storagementioning
confidence: 99%
“…Brazilian Journal of Development, Curitiba, v.9, n.3, p. 10783-10798, mar., 2023 It was observed that the reddish hue (a*) increased during storage, showing a significant difference on all evaluated days. This fact is desirable since anthocyanins present the possibility of replacing the artificial dyes Red 40, Ponceau 4R, Erythrosine and Bordeaux S (Ozela et al, 2007).…”
Section: Stability Of the Powder Dye During Storagementioning
confidence: 99%
“…Pada perlakuan T1, T2, dan T3 aktivitas antioksidan bernilai rendah dapat dikarenakan adanya oksigen, suhu serta paparan cahaya yang masuk. Hal ini sesuai dengan pernyataan Ozela et al, (2007) yang menyatakan bahwa pengaruh paparan produk terhadap cahaya langsung dan oksigen dapat membuat antosianin mengalami degradasi sehingga nilai aktivitas antioksidan pada produk dapat menurun seiring dengan berjalannya waktu. Rendahnya antioksidan ini juga disebabkan oleh proses penepungan yang memerlukan pemanasan yang dapat menurunkan antosianin.…”
Section: Ilustrasi 1 Histogram Aktivitas Antioksidan Yoghurt Ubi Jala...unclassified
“…Basella alba and Basella rubra are the most common forms in the family Basellaceae (Ozela et al 2007). Basella alba is native to Africa and Asia and it is widely cultivated in tropical and sub-tropical arrears where it is used as vegetables.…”
Section: Introductionmentioning
confidence: 99%